Hi
I am struggling to solve the equations:
Given:
d(e^t)/dt =e^t
use the chain rule to find dy/dx:
a) y=e^5t,
b) y=4e^3t
c)y=6e^-2t
(where "^" represents an exponent)
Thanks in advance for any help
Motty
The Chain Rule states,
It can be seen to work through the fact that changes at the rate as moves, speeding up (or slowing down) the rate of change of by that amount.
For instance, if , then moves twice as fast, and .
For problem (a), we note that and . The Chain Rule therefore states,
The same reasoning may be applied to (b) and (c).